Estudio anatómico comparativo de la lámina foliar de Eragrostis (Poaceae: Chloridoideae) de México - Gomez Sanchez, Maricela; Koch, Stephen D. (Instituto de Ecología, A.C., 1998)
Forty-one Mexican species of Eragrostis are compared anatomically. On the basis of the structure of the abaxial epidermis as seen in surface view and the inner structure as seen in cross section of the leaf blade, ten groups are recognized, one with three subgroups. Important differences were found in the presence of papillae; shape of the stomata, microhairs, and silica bodies; position of the vascular bundles; shape of the outer bundle sheath; presence of an adaxial extension of the outer bundle sheath; distribution of the costal abaxial and adaxial sclerenchyma; distribution of the intercostal abaxial sclerenchyma; distribution of the bulliform and colorless cells; and the arrangement and distribution of the chlorenchyma cells. Eragrostis obtusiflora and E. spicata are so distinctive among the species studied that their inclusion in Eragrostis is uncertain.